MENINGKATKAN KEMAMPUAN BERCERITA PADA ANAK USIA DIM BERDASARKAN GAMBAR SERI: Telling story based on the series pictures, the suitability of story with picture - Aisyah, Aisyah (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2011)
In the teaching and learning activity process of Competence Based Curriculum (KBK) in Kindergarten, students demanded to have the story telling ability using the good and right language, pupils expected capable in comprehending the pronunciation, vocabulary and the use of sentence structure in telling story, but the results of student teacher test remained to find some students who have not been able to tell story using series pictures. In regard with the phenomenon, the writer was attracted to make a research on the story telling ability based on the series pictures of the students of the Bunda Kindergarten of Surabaya. As explained in background, the object to be the study in this research was proven as a problem should be researched. For that reason, the writer proposed a problem as follows: What is the story telling ability based on the series pictures of the students of the Bunda Kindergarten of Surabaya. Data analysis method used the descriptive quantitative analysis, population in this research was the entire of group 'B of the Bunda Kindergarten in academic years 2010/2011; the data collection method used the interview, observation, and test methods. Thus, of the results of analysis above it could e concluded that, the story telling sentence structure that suitable with the picture order of the Bunda Kindergarten children was good. Because out of 25 children it was only 7 children had not been able to tell story, due to the children cognitive had not been perfected. Based on the results of this research, thus for the developmental building and the improvement of language teaching quality, in particular the serial picture story telling ability needed attention. It was in order that the pupils capable to accomplish the story telling task properly.